Pengaruh Lingkungan Kerja, Disiplin Kerja, Dan Beban Kerja Terhadap Kinerja Karyawan Pada Rumah Sakit Umum Daerah Kabupaten Bekasi - Adelia, Dinda; Narpati, Bintang; Widjanarko, Wirawan (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to determine the influence of work environment, work discipline, and workload on employee performance at the Regional General Hospital of Bekasi Regency. The research employed a quantitative method with a descriptive approach, and data collection was conducted through the distribution of questionnaires to 85 respondents who are nursing staff in Building D. Data analysis was carried out using multiple linear regression tests with SPSS version 25. The results showed that partially, the work environment variable does not have a significant influence on employee performance. Meanwhile, the variables of work discipline and workload have a positive and significant influence on employee performance. Simultaneously, the three independent variables, work environment, work discipline, and workload have a significant effect on employee performance.